Pengembangan Model Pembelajaran Terpadu Berbasis Budaya Lokal di SD Kota Metro - Tusriyanto Tusriyanto (Jurusan PGMI FTIK IAIN Metro Lampung, 2020)
This research was focused on “Developing Integrated Learning Models Based on Local Culture in Metro City Elementary Schools”. This research has only produced a draft of learning material about“Piil Pesenggiri” which will later be used as a module or teaching material in local culture-basedlearning in Metro City SD. In addition, based on the results of input and discussion in the FGDactivities that learning media are needed in the form of benner standing which gives about the principleof “Pesenggiri Piil” so that it can be read by both teachers and students. Furthermore, learning planswill also be made from the lesson plans to the assessment of integrated learning based on Lampung’slocal culture. Local culture-based learning is needed as an effort to maintain the regional culture ofeach province including Lampung province.